Peran Manajemen Strategik dalam Meningkatkan Hafalan Al-Qur'an di Madrasah Tsanawiyah Purbalingga: Perspektif Sosiologi Lembaga Pendidikan - Isnaini Nurul Hidayati; Muh. Hanif (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the role of strategic management in improving the quality of Qur'an memorization in tahfidz programs at Islamic junior high schools (Madrasah Tsanawiyah) in Purbalingga from the perspective of the sociology of educational institutions. The research employs a qualitative approach with a multiple case study design at MTs Muhammadiyah 01 Purbalingga and MTs Ma’arif NU 05 Majasari. Data were collected through interviews, observations, documentation, and archival records, and analyzed using pattern matching, explanation building, and cross-case synthesis techniques. The findings reveal that the implementation of strategic management—covering strategy formulation, implementation, and evaluation—plays a significant role in enhancing the effectiveness of tahfidz programs. Strategy formulation through SWOT and PESTLE analysis helps schools comprehensively understand internal and external conditions. Strategy implementation supported by resource management and supervision using the Balanced Scorecard improves program execution. Meanwhile, periodic evaluation through monitoring systems and feedback loops enables continuous improvement in students’ memorization achievements. Overall, comprehensive strategic management enhances the quality of Qur'an memorization and fosters competitive advantage in Islamic education institutions.